2001
DOI: 10.4269/ajtmh.2001.65.351
|View full text |Cite
|
Sign up to set email alerts
|

Cyclospora cayetanensis infections among diarrheal patients from Venezuela.

Abstract: Abstract. The prevalence and importance of Cyclospora cayetanensis as an enteropathogen among 71 patients (22-45 years old) with acquired immunodeficiency syndrome (AIDS) and 132 children with diarrhea (0-12 years old) from Venezuela was assessed retrospectively. Two to three stool samples from each patient attending our parasitology laboratory for parasitologic and medical assistance were examined. For identification of the coccidium, modified Ziehl-Neelsen carbolfuchsin staining of formalin-ether stool conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 18 publications
2
10
0
6
Order By: Relevance
“…In a study in Venezuella, Cyclospora oocysts were positive in 9.8% of 71 AIDS patients and 5.3% of 132 children with diarrhea. 2 Alakpa et al found only one diarrhea in 11 cases with C. cayetanensis out of 1109 stool samples. 3 Neither study showed an association of Cyclospora sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in Venezuella, Cyclospora oocysts were positive in 9.8% of 71 AIDS patients and 5.3% of 132 children with diarrhea. 2 Alakpa et al found only one diarrhea in 11 cases with C. cayetanensis out of 1109 stool samples. 3 Neither study showed an association of Cyclospora sp.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] In 1998, the first report about this parasite in the Turkish literature was published. By this time, only few cases were reported and our case is the first one from our region.…”
mentioning
confidence: 99%
“…En estudios realizados en comunidades, las tasas de infección han variado de 0 % a 41,6 % (16-23). La infección es común en niños y el mayor riesgo a la infección sintomática ocurre en los primeros cinco años de vida (3,20,(24)(25)(26). Los estudios basados en la población general indican altos porcentajes de infecciones asintomáticas (17,(20)(21)(22)(27)(28)(29), lo cual sugiere inmunidad al desarrollo de la enfermedad por exposición persistente al coccidio (20,25,29).…”
Section: Cyclospora Cayetanensisunclassified
“…In immunocompromised patients, mostly HIV/AIDS patients with diarrhea, the percentages of Cyclospora infections have ranged from 0 to 36% (Chacin-Bonilla et al, 2001, 2006, 2010. In Colombia, Saudi Arabia, Malaysia, Tanzania, and Cameroon, infection rates of 2.6, 5.9, 4.9, 1.2, and 3.6%, respectively, have been found (Arzuza et al, 2003;Al-Megrin, 2010;Asma et al, 2011;Cegielski et al 1999;Nsagha et al, 2016).Variations in prevalence of infection may be influenced by study design, geographic area, age, and immunologic status of the population studied, seasonal variability of the parasite, methods of detection used, and expertise of the microscopist.…”
Section: Global Distributionmentioning
confidence: 99%